Exploring the Use of Skimming Technique in Teaching Reading at the Seventh Grade of SMP Shirothol Mustaqim - Ahmad Efendi; Eny Maulita Purnama Sari; Fitriana Fitriana; Egi Arasi Sesilia; Nurul Lailatul Azizah; Dewi Nur Hidayatul Isbad (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
Reading comprehension is an essesntial component of EFL learning; however, a lot of students in SMP still have difficulty in understanding English texts due to limited vocabulary, ineffective reading strategies, and dependence on word-by-word translation. The current study aimed to explore the implementation of the skimming technique in teaching reading comprehension among seventh-grade students at SMP Shirothol Mustaqim. The study investigated how the skimming technique was implemented, students’ responses toward skimming technique use, and the challenges encountered during its implementation. A qualitative case study design was used in the study. The study involved one English teacher and 20 students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, document analysis, and supporting reading assessment results. The data were analyzed using Braun and Clarke’s (2021) reflexive thematic analysis. The findings revealed three major themes. First, the skimming technique was systematically integrated into pre-reading, while-reading, and post-reading activities, enabling students to activate prior knowledge and identify the main ideas before engaging in detailed reading. Second, students responded positively to the strategy, demonstrating increased engagement, confidence, participation, and improved reading performance, as reflected in the increase of the mean assessment score from 75 to 100. Third, the implementation faced several challenges, including limited vocabulary knowledge, differences in reading proficiency, and time constraints during classroom instruction. The study concludes that the skimming technique can facilitate more strategic and interactive reading instruction when supported by explicit teacher guidance and appropriate scaffolding.